Proton transfer through the water gossamer - Hassanali, Ali; Giberti, Federico; Cuny, Jerome; Kuehne, Thomas D.; Parrinello, Michele (Proceedings of the National Academy of Sciences of the United States of America, 2013)
The diffusion of protons through water is understood within the framework of the Grotthuss mechanism, which requires that they undergo structural diffusion in a stepwise manner throughout the water network. Despite long study, this picture oversimplifies and neglects the complexity of the supramolecular structure of water. We use first-principles simulations and demonstrate that the currently accepted picture of proton diffusion is in need of revision. We show that proton and hydroxide diffusion occurs through periods of intense activity involving concerted proton hopping followed by periods of rest. The picture that emerges is that proton transfer is a multiscale and multidynamical process involving a broader distribution of pathways and timescales than currently assumed. To rationalize these phenomena, we look at the 3D water network as a distribution of closed directed rings, which reveals the presence of medium-range directional correlations in the liquid. One of the natural consequences of this feature is that both the hydronium and hydroxide ion are decorated with proton wires. Thesewires serve as conduits for long proton jumps over several hydrogen bonds.
CRIS-Team Scopus Importer:2023-03-20